Variable Structure in the Pds 70 Disc and Uncertainties in Radio-Interferometric Image Restoration - Carcamo-Vasquez, M (Oxford University Press, 2022)
The compact mm-wavelength signal in the central cavity of the PDS 70 disc, revealed by deep ALMA observations, is aligned with unresolved H αemission, and is thought to stem from a circumplanetary disc (CPD) around PDS 70c. We revisit the available ALMA data on PDS 70c with alternative imaging strategies, and with special attention to uncertainties and to the impact of the so-called JvM correction , which is thought to impro v e the dynamic range of restored images. We also propose a procedure for the alignment and joint imaging of multi-epoch visibility data. We find that the JvM correction exaggerates the peak signal-to-noise of the data, by up to a factor of 10. In the case of PDS 70, we reco v er the detection of PDS 70c from the 2019 July data, but only at 8 σ. Ho we ver, its non-detection in 2017 Dec. suggests that PDS 70c is variable by at least 42 per cent ±13 per cent o v er a 1.75 yr time-span, so similar to models of the H αvariability. We also pick up fine structure in the inner disc, such that its peak is offset by ∼0 . 04 from the disc centre. The inner disc is variable too, which we tentatively ascribe to Keplerian rotation as well as intrinsic morphological changes. © 2022 The Author(s).